Silica supported amorphous molybdenum catalysts prepared via sol–gel method and its catalytic activity - Adam, Farook; Mohamed Iqbal, Mohammad Anwar (Elsevier Inc., 2011)
Silica supported amorphous molybdenum catalysts had been synthesized in alkali, neutral and acidic medium via sol–gel technique. The catalysts were found to be amorphous and free from bulk MoO3. UV–Vis diffuse reflectance analysis and XPS analysis indicated the co-existence of Mo5+ and Mo6+ species when the incorporation was done in acidic medium. The catalytic activity was tested in the liquid phase oxidation of styrene by using hydrogen peroxide as oxidant. The catalyst prepared in acidic medium showed better catalytic activity compared to the catalysts prepared in alkali and neutral medium. The co-existence of Mo5+ and Mo6+ species is believed to enhance the catalytic activity. Benzaldehyde was the major product detected. The structure of the catalyst was proposed based on the results obtained from XPS, 29Si MAS NMR, UV–Vis diffuse reflectance and FT-IR spectroscopy.